PENERAPAN PEMBELAJARAN GURU PAI DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK - FERDINAND, EVA OKTAVIANI (UNISAN JURNAL, 2025)
This study aims to analyze the management of Islamic boarding schools (pondok pesantren) in shaping students’ (santri) independence. The primary focus of this research lies in the strategies implemented by the pesantren to develop independent character among the students, encompassing aspects of education, skills development, and the management of daily life. This research employs a qualitative approach using a case study method, which enables an in-depth exploration of the phenomena occurring within the pesantren environment. Data collection was conducted through direct observation of students’ activities in the boarding school, in-depth interviews with pesantren caretakers, students, and alumni, as well as analysis of documentation related to the institution’s managerial policies. The data analysis technique used in this study adopts the interactive model proposed by Miles and Huberman, which consists of three main stages: data reduction, data display, and conclusion drawing/verification.